Calculation and Analysis of Aircraft Pollutant Emission Based on Time Wake Separation Mode under Coastal Airport and Headwind Conditions - Pan Wei-Jun; Zhang Heng-Heng; Zhang Xiao-Lei; Wu Tian-Yi (Journal of Advanced Transportation)
During the final approach, the headwind leads to a reduction of landing rate, which affects the achieved capacity and the predictability of operation, time, fuel efficiency, and environmental pollution. Under headwind conditions, ground speed decrease results in increased flight time. Time-based separation (TBS) changes the separation rule of the final approach, which changes the distance separation between two aircrafts into a time separation. This paper introduces the time-based separation (TBS) based on the distance-based separation (DBS). According to the aircraft landing schedule of each airport, the ICAO (International Civil Aviation Organization) aircraft engine emission database, Boeing Fuel Flow Method 2 (BFFM2), and meteorological data of Pu-dong airport, this study uses the modified P3-T3 aviation pollutant emission model to calculate, respectively, the fuel consumption and pollutant emissions based on distance separation mode and time separation mode. According to the calculation results, TBS operation mode can save 32.52%, 19.12%, and 30.41% fuel, reduce 28.93%, 17.9%, and 29.29% CO, 31.02%, 19.36%, and 33.78% HC, 30.85%, 16.42%, and 28.67% NOx, respectively, compared with the DBS operation mode at three stages of the day. It ends that TBS has an obvious optimization effect on fuel consumption and pollutant emission compared with DBS from data.